1996
DOI: 10.1093/oxfordjournals.ndt.a027095
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ambulatory blood pressure monitoring data to echocardiographic findings in haemodialysis patients

Abstract: ABPM is necessary to assess the adequacy of BP control, and is well correlated to end-organ damage of HT in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 20 publications
4
40
0
1
Order By: Relevance
“…Standardized techniques were used by several studies that were included in this review. Erturk et al (37) did not observe substantial differences in the recordings when using a standardized technique, but others (23,30,33,34,36,40) did. Studies that used the standardized measurements had as much variability in the difference between pre/postdialysis BP and ambulatory measurements as did nonstandardized studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Standardized techniques were used by several studies that were included in this review. Erturk et al (37) did not observe substantial differences in the recordings when using a standardized technique, but others (23,30,33,34,36,40) did. Studies that used the standardized measurements had as much variability in the difference between pre/postdialysis BP and ambulatory measurements as did nonstandardized studies.…”
Section: Discussionmentioning
confidence: 90%
“…The average ages reported varied from 31.6 to 61.2 yr. At least six studies excluded patients with diabetes (22,32,(35)(36)(37)(38). The average interdialytic weight gain ranged between 1.3 and 4.5 kg.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…It has been reported that ambulatory blood pressure monitoring (ABPM) data in dialysis patients are a better predictor for development of LVH and cardiovascular mortality than casual blood pressure (BP) measurements. 4,5 Casual BP measurements are far from being ideal to reflect BP levels precisely in dialysis patients and adjusting antihypertensive treatment according to casual BP measurements may cause an inadequate BP control. ABPM allows a better assessment in the course of BP levels during the day.…”
Section: Introductionmentioning
confidence: 99%
“…ABPM allows a better assessment in the course of BP levels during the day. 5,6 It was also reported that abnormal BP rhythm, which is common in patients with endstage renal failure, might be associated with target organ damage resulting from hypertension in women. 7 Numerous studies with 24-h ABPM have been reported in haemodialysis and CAPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is hypothesized that these patients are exposed to higher blood pressures over 24 h and more frequent target organ damage. Related studies have revealed that nighttime blood pressure is associated with LVH [18][19][20][21] and is a predictor of negative cardiovascular outcomes in patients undergoing HD. 22,23 One study reported that cardiovascular survival was worse in patients with the ND blood pressure pattern compared to patients with the D blood pressure pattern, and it stated that an elevated 24 h pulse pressure and nighttime systolic blood pressure were associated with cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%